Return of the lysergamides. Part I: Analytical and behavioural characterization of 1‐propionyl‐d‐lysergic acid diethylamide (1P‐LSD). Issue 9 (12th October 2015) - Brandt, Simon D.; Kavanagh, Pierce V.; Westphal, Folker; Stratford, Alexander; Elliott, Simon P.; Hoang, Khoa; Wallach, Jason; Halberstadt, Adam L.
Abstract : 1‐Propionyl‐ d ‐lysergic acid diethylamide hemitartrate (1P‐LSD) has become available as a 'research chemical' in the form of blotters and powdered material. This non‐controlled derivative of d ‐lysergic acid diethylamide (LSD) has previously not been described in the published literature despite being closely related to 1‐acetyl‐LSD (ALD‐52), which was developed in the 1950s. This study describes the characterization of 1P‐LSD in comparison with LSD using various chromatographic and mass spectrometric methods, infrared and nuclear magnetic resonance spectroscopy. An important feature common to LSD and other serotonergic hallucinogens is that they produce 5‐HT2A ‐receptor activation and induce the head‐twitch response (HTR) in rats and mice. In order to assess whether 1P‐LSD displays LSD‐like properties and activates the 5‐HT2A receptor, male C57BL/6 J mice were injected with vehicle (saline) or 1P‐LSD (0.025–0.8 mg/kg, IP) and HTR assessed for 30 min using magnetometer coil recordings. It was found that 1P‐LSD produced a dose‐dependent increase in HTR counts, and that it had 38% (ED50 = 349.6 nmol/kg) of the potency of LSD (ED50 = 132.8 nmol/kg). Furthermore, HTR was abolished when 1P‐LSD administration followed pretreatment with the selective 5‐HT2A receptor antagonist M100907 (0.1 mg/kg, SC), which was consistent with the concept that the behavioural response was mediated by activation of the 5‐HT2A receptor. These results indicate that 1P‐LSD produces LSD‐like effects in mice, consistent with its classification as a serotonergic hallucinogen. Nevertheless, the extent to which 1P‐LSD might show psychoactive effects in humans similar to LSD remains to be investigated. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : 1‐Propionyl‐ d ‐lysergic acid diethylamide (1P‐LSD) is a newly emerging 'research chemical'. This investigation presents the analytical characterization and shows that 1P‐LSD exhibited LSD‐like properties, consistent with its classification as a serotonergic hallucinogen. 1P‐LSD dose‐dependently induced head‐twitch response (HTR) counts in male C57BL/6 J mice (ED50 = 349.6 nmol/kg). The HTR was not induced when mice were treated with the 5‐HT2A receptor antagonist M100907, which confirmed that the behavioural response was mediated by activation of the 5‐HT2A receptor.